2010
DOI: 10.1042/bj20100516
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent probe partitioning in giant unilamellar vesicles of ‘lipid raft’ mixtures

Abstract: Direct visualization of raft-like l(o) (liquid-ordered) domains in model systems and cells using microscopic techniques requires fluorescence probes with known partitioning preference for one of the phases present. However, fluorescent probes may display dissimilar partitioning preferences in different lipid systems and can also affect the phase behaviour of the host lipid bilayer. Therefore a detailed understanding of the behaviour of fluorescent probes in defined lipid bilayer systems with known phase behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 40 publications
11
106
0
1
Order By: Relevance
“…To see whether glycol chitosan-FITC can visualize the lipid raft domains in a more cell-like geometry, GUVs composed of DOPC/SM/Chol (1:1:1) containing 1 mol% of LR-DOPE were prepared and observed under a confocal fluorescence microscope after interacting with 20 µg/mL glycol chitosan-FITC. The appearance of the fluorescent lipid-labeled GUVs(Figure 6) was similar to that in the previous work 36. The confocal imaging results of GUVs also indicate that glycol chitosan-FITC could stain lipid raft domains preferentially(Figure 6), in line with that of SLBs (Figure 2).…”
supporting
confidence: 83%
“…To see whether glycol chitosan-FITC can visualize the lipid raft domains in a more cell-like geometry, GUVs composed of DOPC/SM/Chol (1:1:1) containing 1 mol% of LR-DOPE were prepared and observed under a confocal fluorescence microscope after interacting with 20 µg/mL glycol chitosan-FITC. The appearance of the fluorescent lipid-labeled GUVs(Figure 6) was similar to that in the previous work 36. The confocal imaging results of GUVs also indicate that glycol chitosan-FITC could stain lipid raft domains preferentially(Figure 6), in line with that of SLBs (Figure 2).…”
supporting
confidence: 83%
“…25 Alternatively, NBD probes can be used as acceptors to chromophores including diphenylhexatriene 26,27 or trans-parinaric acid, 28 or even as donors and acceptors simultaneously in homo-FRET studies. 20 Several fluorescence spectroscopic and microscopic studies have also indicated that, contrary to the vast majority of membrane fluorescent probes, doubly saturated long-chained NBD-diC n PE partitions favourably to liquid ordered (lo) phases in systems displaying lo/liquid disordered phase coexistence, 22,24,29,30 although the phase preference depends both on the probe acyl chain length and the composition of the underlying lipid mixture. 17,31 Despite their wide use in membrane biophysics, the behaviour of NBD-diC n PE probes has so far lacked a characterization using MD.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the quantum efficiency and brightness of most of the organic dyes are higher than for fluorescent proteins. Cholesterol (Boldyrev et al 2007;Holtta-Vuori et al 2008;Marks et al 2008;Oreopoulos and Yip 2009), Sphingomyelin (Marks et al 2008;Eggeling et al 2009;Tyteca et al 2010), GM1 (Coban et al 2007;Eggeling et al 2009;Mikhalyov et al 2009), PC, and PE (Baumgart et al 2007;Juhasz et al 2010) are some of the lipids that are often conjugated to organic dyes. Additionally, fluorescently labeled membrane-binders, like choleratoxin, are used to label, for example, the GMs on the cell surface (Middlebrook and Dorland 1984).…”
Section: Fluorescent Probes To Study Lipid Dynamicsmentioning
confidence: 99%